2005
DOI: 10.1021/ja054599k
|View full text |Cite
|
Sign up to set email alerts
|

Air-Breathing Laminar Flow-Based Microfluidic Fuel Cell

Abstract: This communication reports the design and characterization of an air-breathing laminar flow-based microfluidic fuel cell (LFFC). The performance of previous LFFC designs was cathode-limited due to the poor solubility and slow transport of oxygen in aqueous media. Introduction of an air-breathing gas diffusion electrode as the cathode addresses these mass transfer issues. With this design change, the cathode is exposed to a higher oxygen concentration, and more importantly, the rate of oxygen replenishment in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
242
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(261 citation statements)
references
References 14 publications
1
242
4
3
Order By: Relevance
“…The typical open-circuit voltage of an air-breathing LFFC with similar fuel and electrolyte is in the range of 0.7 V to 0.9 V [5]. Since the microfluidic fuel cell takes the advantage of co-laminar streams, changes in flow rate will affect the molecular diffusion and consequently the cell performance.…”
Section: Concentration Distribution Of Formic Acidmentioning
confidence: 99%
“…The typical open-circuit voltage of an air-breathing LFFC with similar fuel and electrolyte is in the range of 0.7 V to 0.9 V [5]. Since the microfluidic fuel cell takes the advantage of co-laminar streams, changes in flow rate will affect the molecular diffusion and consequently the cell performance.…”
Section: Concentration Distribution Of Formic Acidmentioning
confidence: 99%
“…As a result, the water management is not needed [3]. Furthermore, the structures of membraneless micro fuel cells are very simple 2 International Journal of Electrochemistry and easy to miniaturize [4], so that light and stackable fuel cells can be fabricated with simple microelectromechanical systems (MEMS) [5,6]. The flexibility and the performance implications of operating membraneless sodium perborate fuel cell (MLSPBFC) under "acid-alkaline media, " that is, one electrode is acidic and the other one is alkaline condition, will be the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Although the enhancement of single M 2 FC performance is not within the scope of this study, it is noted that many single cell studies have reported M 2 FC performance ten-fold that of the 21 present study through employing certain combinations of fuel/oxidant, advanced catalysts or cell designs [13,15,52].…”
Section: The Effect Of the Number Of Cells In Seriesmentioning
confidence: 78%